World Bank Group And International Monetary Fund Support For Debt Relief Under The Common Framework And Beyond. (Policy Papers; Policy Paper ;, 2021)
This paper discusses World Bank and IMF support for addressing fiscal and debt distress in IDA countries, with emphasis on strong continued concessional flows for green, resilient, and inclusive development.